Availability and usage of health insuran policies amoung inward patients at government and private hospitals in Gampaha District - Wickramanayake, H.M.K (My University, 2005)
A total of 550 in-ward patients participated in the study and data were collected using a pretested Interviewer administered questionnaire. Samurdhi health insurance (SHI) was the most common type of insurance in the public sector (13 percent ). In the private hospital, 38 percent of patients had health insurance cover and Employer sponsored health insurance was the most common type (24 percent ). It was found that the availability of Private health insurance (individual and group) and Agrahara health insurance (AHI) among in-ward patients in the public hospitals were 5.4 percent and 4.4 percent respectively The demographic and socio-economic characteristics of the insured patients showed that Private Health Insurance (PHI) and AHI were mainly restricted to the middle and upper income groups, and the working age (19-60 years) population in the work force All of the insured patients in the private hospitals covet but they had got admitted to public hospitals cover but they had got admitted to public hospitals for treatment as they could not afford the high cost of private hospitals care. The benefit claming rate among in-ward patients in the private hospitals was 96 for 100 episodes of in-ward treatment and it was 12 in the public hospitals. The benefit claiming rate among OPD/GP patients in the private sector was 24 for 100 episodes of OPD/ GP care.